RESPONSIBILITAS MANGGA (Mangifera indica) BENIH KERNEL TERHADAP TEKNIK PENGOLAHAN KANDUNGAN GIZI DAN ANTINUTRISIONAL - Muhammad Chabib Ichsan (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2014)
The nutritive value of raw and processed mango seed kernel (MSK) was investigated using proximate analysis, metabolizable energy and anti-nutritional factors. Nine processing methods were carried on the raw seeds. The raw seeds had values that were significantly (p